(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction: Glaucoma refers to chronic diseases that require constant treatment. Conservative treatment of glaucoma involves the continuous assigning of local hypotensive medications for a long time to maintain normal range of intraocular pressure (IOP). Objective: To examine the efficacy of Latanoks medication in clinical practice with patients having primary open-angle glaucoma. Material and methods: 20 patients (30 eyes) have been under the observation with primary open-angle glaucoma stage I-III. All the patients were transferred to Latanoks monotherapy due to the lack of the intraocular pressure compensation. Tonometry, tonography, electronic static perimetry were performed at the beginning and the end of the observation period. Results: The use of Latanoks medication for the treatment of patients with an open-angle glaucoma within three months has led to a decrease of tonography Po index from an average (20.0 ± 6.0) mm Hg to (14.9 ± 3.0) mm Hg (p < 0.0003). The use of Latanoks for the treatment of patients with open-angle glaucoma within three months has led to a decrease of IOP (by Maklakov) from an average (22.8 ± 5.0) mm Hg. to (17.6 ± 2.0) mm Hg (p < 0.0002) and also has allowed to keep the visual field indicators stable for three months. Conclusion: Latanoks is an effective hypotensive medication that does authentically lower IOP and helps to save the visual field.